The use of febuxostat for gout in Hospital Tengku Ampuan Afzan (HTAA) Kuantan - Abdullah, Hilmi (2017)
Febuxostat is a non-purine-selective oral xanthine oxidase inhibitor drug, and is an alternative to Allopurinol to lower serum uric acid in gout patients. It is probably more effective than Allopurinol, however, its use is limited because of its cost and availability. Allopurinol has been the mainstay treatment for gout for about 50 years. However, its use has been associated with allergic reactions especially in patients with renal impairment.The objective of this study was to describe HTAA Rheumatology Unit experiences with Febuxostat in the management of gout.